Benzophenones and synthetic progestin in wastewater and sediment from farms, WWTPs and receiving surface water: distribution, sources, and ecological risks. Issue 50 (27th September 2021) - Wang, Siqi; Huo, Zhuhao; Gu, Jianzhong; Xu, Gang
Abstract : The occurrence, source and ecological risk of BPs and synthetic progestin in farms, WWTPs and their receiving river were investigated. Abstract : Farms and wastewater treatment plants (WWTPs) are important sources of endocrine disruptors, which may have potential adverse effects on the nearby receiving river and potential human health risks. Benzophenone (BPs) and synthetic progestin were determined in water and sediment samples of the discharge source and receiving river. BPs and synthetic progestin ranged from not detected (N.D.) to 400.53 ng L −1 in water samples and from N.D. to 359.92 ng g −1 dw in sediment, respectively, and benzophenone-3 (BP-3) and ethinyl estradiol (EE2) were the main detected objects. Correlation analysis showed that pollutants discharged from livestock farms were the main contributor to the receiving river. The distribution of pollutants in different regions was related to higher population density and livestock activities. Predicted no-effect concentrations (PNECs) were investigated for ecological risk assessment in the study area, and 86% of the samples exceeded the baseline value of chronic toxicity. Benzophenone-1 (BP-1), benzophenone-3 (BP-3), 4-hydroxybenzophenone (4-OH-BP) and benzophenone (BP) were identified as the main substances that caused medium risk in the aquatic ecosystem. Therefore, BPs and synthetic progesterone should be given more attention in the future.